On some aspects of the generalized Petersen graph - V. Yegnanarayanan (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2017)
Let p 3 be a positive integer and let k 1, 2, ..., p-1 p/2 floor. The generalized Petersen graph GP(p,k) has its vertex and edge set as V(GP(p, k)) = {u_i : i Zp} {u_i^′ : i Z_p} and E(GP(p, k)) = {u_i u_i+1 : i Z_p} {u_i^′ u_i+k^′ Z_p} {u_iu_i^′ : i Z_p}. In this paper we probe its spectrum and determine the Estrada index, Laplacian Estrada index, signless Laplacian Estrada index, normalized Laplacian Estrada index, and energy of a graph. While obtaining some interesting results, we also provide relevant background and problems.